Pengaruh Pengawasan, Akuntabilitas, Dan Transparansi Terhadap Kinerja Keuangan Pada Kantor SKPK Kota Langsa - Gusliandi, Farhan; Lubis, Nasrul Kahfi; Azhar, Iqlima (Jurnal Manajemen Akuntansi (JUMSI), 2023)
At this writing, it has a goal, namely to be able to study about an influence on supervision, accountability and transparency, namely on financial performance in the SKPK office in Langsa City. In the writer's research, in order to get some data, the writer used a method, namely distributing questionnaires to a section related to the research made by this writer, so in this way a sample can be taken, then the writer uses a sample, namely the sample is specific, namely all members of the population, the writer needs to draw data by testing the instrument, then there is also a test using classical assumptions and using an regression analysis of multiple linearity. In the end, the conclusion of the hypothesis testing is by showing that (1) the existence of an oversight has a significant effect on financial performance at the SKPK office in Langsa City (2) accountability has a significant effect on performance at the SKPK office in Langsa City (3) Transparency has a significant influence on financial performance at the Langsa City SKPK office. Therefore all hypotheses will be proposed and then accepted.